Cardiovascular Mitochondrial Dysfunction Induced by Cocaine: Biomarkers and Possible Beneficial Effects of Modulators of Oxidative Stress. (16th May 2017) - Graziani, Manuela; Sarti, Paolo; Arese, Marzia; Magnifico, Maria Chiara; Badiani, Aldo; Saso, Luciano
Abstract : Cocaine abuse has long been known to cause morbidity and mortality due to its cardiovascular toxic effects. The pathogenesis of the cardiovascular toxicity of cocaine use has been largely reviewed, and the most recent data indicate a fundamental role of oxidative stress in cocaine-induced cardiovascular toxicity, indicating that mitochondrial dysfunction is involved in the mechanisms of oxidative stress. The comprehension of the mechanisms involving mitochondrial dysfunction could help in selecting the most appropriate mitochondria injury biological marker, such as superoxide dismutase-2 activity and glutathionylated hemoglobin. The potential use of modulators of oxidative stress (mitoubiquinone, the short-chain quinone idebenone, and allopurinol) in the treatment of cocaine cardiotoxic effects is also suggested to promote further investigations on these potential mitochondria-targeted antioxidant strategies.